Assessment of solar shading strategies in low-income tropical housing: the case of Uganda. Issue 6 (5th October 2018) - Hashemi, Arman
Abstract : Developing countries in tropical and subtropical areas will be the worst hit by climate change. Very little research has been done to assess the impact of climate change on thermal comfort in low-income housing in these regions. The effects of solar shading strategies and solar absorptance properties of walls and roofs on thermal comfort in Ugandan low-income housing are studied in this paper. Various shading strategies including curtains, roof and window overhangs, veranda and trees as well as effects of painting on solar heat gain and thermal comfort are modelled using EnergyPlus software. An adaptive approach for naturally ventilated buildings defined by the European Committee for Standardization standard BS EN 15251:2007 is used to assess the conditions. According to the results, solar shading is less effective in meeting thermal comfort requirements and it should be used in conjunction with other strategies to achieve desirable results. White painting, in contrast, significantly improved the conditions and significantly reduced the risk of overheating. Solar shading proved to be effective during the hottest periods of the year, reducing the risk of extreme overheating by up to 52%.